(untitled) - Lauer, Robert H. (Boston, 2002)
Focusing on quality of life, this text defines what a social problem is and then addresses specific issues—for example, how can one gain a sociological understanding of social problems? What kinds of critical thinking should one engage in and what kinds should one avoid in attempting to understand social problems? How is the quality of one's life affected by particular problems? What causes these problems and how can we resolve them? Part One establishes key approaches to social problems; the remaining parts discuss the social problems that most acutely impact the quality of our lives.
Keywords: Quality of life,Social problems,United states; Social conditions; United states